Key Financial Factors Influencing Investment: Profitability, Liquidity, Leverage, Size, and Stock Price: Faktor Keuangan yang Membentuk Keputusan Investasi: Profitabilitas, Likuiditas, Leverage, Ukuran, dan Harga Saham - Mukhammad Amar Musliq; Sarwenda Biduri (Universitas Muhammadiyah Sidoarjo, 2022)
This study examines the influence of profitability, liquidity, leverage, size, and stock prices on investment decisions in the food and beverage industry, focusing on companies listed on the Indonesia Stock Exchange between 2016 and 2019. The purposive sampling method was employed, resulting in a sample of 13 food and beverage companies. Multiple linear regression analysis was used to analyze secondary data. The findings reveal that profitability, liquidity, leverage, size, and stock prices significantly affect investment decisions in the food and beverage sector during the study period. These results imply that investors consider these financial factors when making investment decisions, highlighting the importance of assessing profitability, liquidity, leverage, size, and stock prices for effective investment strategies in the global food and beverage industry. Highlights: Profitability's Impact: The study reveals that profitability significantly influences investment decisions in the food and beverage industry. Liquidity Matters: The findings emphasize the importance of liquidity in shaping investment decisions within the food and beverage sector. Leverage and Decision Making: The study highlights the effect of leverage on investment decisions in food and beverage companies, providing valuable insights for investors. Keywords: Profitability, Liquidity, Leverage, Size, Stock Price